1994
DOI: 10.1099/0022-1317-75-10-2559
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbiotic bacteria associated with circulative transmission of potato leafroll virus by Myzus persicae

Abstract: In order to understand the molecular mechanisms underlying circulative transmission of potato leafroll virus (PLRV) by aphids, we screened Myzus persicae proteins as putative PLRV binding molecules using a virus overlay assay of protein blots. In this way, we found that purified PLRV particles exhibited affinity for five aphid proteins. The one most readily detected has an M r of 63K, and was identified as symbionin. This is the predominant protein synthesized by the bacterial endosymbiont of the aphid and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 31 publications
(26 reference statements)
2
119
0
3
Order By: Relevance
“…In aphids and whiteflies, GroEL homologues are circulating in the haemolymph outside the bacterial cells [58]. It has been shown that virions bind to these GroEL homologues, thereby escaping destruction by the vector's immune system and allowing virus transmission [58,59]. It is not always clear whether GroEL of facultative or primary symbionts is involved in this process, and therefore it is unknown how much variability there is within the vector species.…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In aphids and whiteflies, GroEL homologues are circulating in the haemolymph outside the bacterial cells [58]. It has been shown that virions bind to these GroEL homologues, thereby escaping destruction by the vector's immune system and allowing virus transmission [58,59]. It is not always clear whether GroEL of facultative or primary symbionts is involved in this process, and therefore it is unknown how much variability there is within the vector species.…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%
“…GroEL is a protein produced by bacteria. In aphids and whiteflies, GroEL homologues are circulating in the haemolymph outside the bacterial cells [58]. It has been shown that virions bind to these GroEL homologues, thereby escaping destruction by the vector's immune system and allowing virus transmission [58,59].…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%
“…Interactions between the virus capsid and aphid components at all of these sites may be important in conferring vector specificity (12,14). Finally, in the hemocoel, binding of the virus to symbionin, a chaperonin secreted into the hemolymph by endosymbiotic bacteria of the aphid, is known to stabilize luteoviruses in a vector-nonspecific manner (9,32,33).…”
Section: Beet Western Yellows Virus (Bwyv) Is a Member Of Thementioning
confidence: 99%
“…5A). For brevity, we shall refer to the wild-type sequence PVT (32)(33)(34) to which these mutations map as the PVT patch.…”
Section: Mutations In the Conserved Portion Of The Bwyv Rtdmentioning
confidence: 99%
“…Viruses of the family Luteoviridae belongs to ssRNA plant viruses, divided into three genera: Enamovirus, Luteovirus and Polerovirus [5]. Members of this family infect a broad range of mono-and dicotyledonous plants that they exclusively replicate in the phloem tissue [6]. PLRV infects potato plants, causing economic losses on the yield [7,8].…”
Section: Introductionmentioning
confidence: 99%